A randomized controlled trial of project-based learning for middle-school financial literacy - Mishra, Ishaan; Orosz, Gábor (Frontiers in Education, 2026)
Financial literacy remains low among U.S. middle school students, while engagement with traditional instruction often declines. This class-randomized, posttest-only trial (two intact sections) compared Project-Based Learning and Standards-Based Learning in a budgeting unit delivered via Nearpod® across three 40-min class sessions. Sixth-grade students designed a class-trip budget (Project-Based Learning) or received structured lectures with practice activities (Standards-Based Learning). A 12-item posttest (7 multiple-choice + 5 open-ended) assessed vocabulary knowledge and applied reasoning. Project-Based Learning outperformed Standards-Based Learning on the combined score: Project-Based Learning n = 23, M = 6.65, SD = 1.40; Standards-Based Learning n = 25, M = 5.64, SD = 1.13; Welch’s t(42.39) = 2.74, p = 0.009; Hedges’ g = 0.78, 95% CI [0.19, 1.36]. The intraclass correlation coefficient (ICC = 0.22) indicated notable class-level clustering, so student-level inferences are interpreted as exploratory. Findings provide causal evidence that even a brief, decision-focused Project-Based Learning intervention enhances comprehension and application of budgeting concepts more effectively than traditional instruction, highlighting the potential of project-based curricula as authentic and scalable approaches to strengthening middle-school financial literacy.